Indigenous people, organized crime and natural resources: borders, incentives and relations - Uhm, Daan P. van (Critical criminology, 2021)
This article explores the relationship between the Emberá-Wounaan and Akha Indigenous people and organized crime groups vying for control over natural resources in the Darién Gap of East Panama and West Colombia and the Golden Triangle (the area where the borders of Laos, Myanmar (Burma), and Thailand meet), respectively. From a southern green criminological perspective, we consider how organized crime groups trading in natural resources value Indigenous knowledge. We also examine the continued victimization of Indigenous people in relation to environmental harm and the tension between Indigenous peoples’ ecocentric values and the economic incentives presented to them for exploiting nature. By looking at the history of the coloniality and the socioeconomic context of these Indigenous communities, this article generates a discussion about the social framing of the Indigenous people as both victims and offenders in the illegal trade in natural resources, particularly considering the types of relationships established with dominant criminal groups present in their ancestral lands.